2003
DOI: 10.1042/bj20020933
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide-dependent consumption of nitric oxide in biological media may confound in vitro experiments

Abstract: NO functions ubiquitously as a biological messenger but has also been implicated in various pathologies, a role supported by many reports that exogenous or endogenous NO can kill cells in tissue culture. In the course of experiments aimed at examining the toxicity of exogenous NO towards cultured cells, we found that most of the NO delivered using a NONOate (diazeniumdiolate) donor was removed by reaction with the tissue-culture medium. Two NO-consuming ingredients were identified : Hepes buffer and, under lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 38 publications
1
41
2
Order By: Relevance
“…Although the lower amounts of NO detected could be due to the partial release or formation of alternative nitrogen oxide species such as NO -or NO 2 , nitroxyl formation would be unlikely for the secondary amine-derived substrates involved and significant oxidation would be unexpected at the concentration levels employed. Keynes et al have reported that NO delivered via a diazeniumdiolate was consumed by reaction with ingredients, Hepes buffer and riboflavin, present in a tissue-culture medium [32]. A mechanism involving formation of superoxide radical (O 2 ▪ -) through oxidation of Hepes followed by the rapid reaction of superoxide with NO to form peroxynitrite was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lower amounts of NO detected could be due to the partial release or formation of alternative nitrogen oxide species such as NO -or NO 2 , nitroxyl formation would be unlikely for the secondary amine-derived substrates involved and significant oxidation would be unexpected at the concentration levels employed. Keynes et al have reported that NO delivered via a diazeniumdiolate was consumed by reaction with ingredients, Hepes buffer and riboflavin, present in a tissue-culture medium [32]. A mechanism involving formation of superoxide radical (O 2 ▪ -) through oxidation of Hepes followed by the rapid reaction of superoxide with NO to form peroxynitrite was proposed.…”
Section: Discussionmentioning
confidence: 99%
“…The result is the formation of peroxynitrite, a reactive oxidizing species causing direct or radical-mediated covalent modifications to proteins and other molecules (24) and the generation of chemicals containing releasable NO (25,26). The inclusion of superoxide dismutase and urate at appropriate concentrations (22), guarded against peroxynitrite formation in our experiments. Even so, active secondary NO sources were formed when high NO concentrations were applied, particularly in Hepes buffer (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The use of Hepes buffer (used at 50 mM in the experiments of Cary et al) is already known to be hazardous. Hepes catalyses the production of superoxide anions, which rapidly combine with NO, even at the low NO concentrations activating GC-coupled receptors (22,23). The result is the formation of peroxynitrite, a reactive oxidizing species causing direct or radical-mediated covalent modifications to proteins and other molecules (24) and the generation of chemicals containing releasable NO (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…NO levels in the superfusate were measured continuously in a small, closed fluid reservoir immediately upstream from the recording chamber. Uric acid (30 M) was added to the superfusate to reduce the levels of NO 2 resulting from NO oxidation (Keynes et al, 2003).…”
Section: Nitric Oxide Rampmentioning
confidence: 99%